Exploring the Landscape of Restless Legs Syndrome: A Cross-sectional Study - Stella Maris Valiensi; Agustín Leandro Folgueira; Arturo D. C. Garay; Noelia Maria Enriz; Sofia Caporale; Daniela L. Giardino (Neurological Sciences and Neurophysiology)
Background: The prevalence of restless legs syndrome (RLS) is 20.2% in our country, Argentina, but the association with sleep quality, mood disorders, sleeping with pets, and other related variabilities has not been evaluated yet. The objectives include to explore the presence of RLS using two validated questionnaires in Spanish and evaluate the association of RLS with some sociodemographic variables, medical history, pharmacological history of co-sleeping pets and variables related to sleep quality and mood disorders. Materials and Methods: We conducted a cross-sectional observational study. We chose convenience sampling, distributing anonymous and self-administered online questionnaires through social networks and E-mail. We investigated the presence of RLS using two validated questionnaires in Spanish: Single Question on Restless Legs Syndrome (RLSQ-1) and the Practitioner’s RLS Screening Questionnaire (PRLS-SQ). In addition, sleep quality was assessed by the Pittsburgh Sleep Quality Index; depression/anxiety symptoms were assessed by the Patient Health Questionnaire and, in the same survey, we asked about sociodemographic data, medical history, and questions in related to the habit of sleeping with pets. Results: A total of 2081 participants responded. RLS prevalence was 11% by RLSQ-1 and 14.8% by PRLS-SQ. The RLSQ-1 identified an association with poor sleep quality (P = 0.02/Odds ratio [OR] = 2.8); diabetes (P = 0.00/OR = 2.5). With PRLS-SQ, we found a higher risk of RLS in participants with poor sleep quality (P = 0.00/OR = 1.8); anxiety (P = 0.00/OR = 1.8); depression (P = 0.00/OR = 1.5); apnea (P = 0.00/OR = 2.5); and a lower risk in those who sleep with pets (P = 0.04/OR = 0.75). Conclusions: Both RLS questionnaires identified an association between RLS and poor-quality sleep. Furthermore, the RLSQ-1 found associations with anxiety symptoms, diabetes diagnosis, and taking some drugs to sleep. The PRLS-SQ identified links to symptoms of depression and anxiety, sleep apnea, as well as a possible protective effect in co-sleeping with pets.